1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

1 = -1

  1. May 29, 2008 #1
    Hey Everyone,

    A while back I found this cool little proof that showed 1 = -1. Now I am fully aware there was a little cheat in there somewhere, but I have lost the little proof. Has anyone come across it, or have anything similar? I just think it's cool, even though in one of the steps there is a mistake. I know it starts with like rooting one, and then putting 1 = (-1)(-1) etc.


  2. jcsd
  3. May 29, 2008 #2
    I got another version:

    [tex] \frac{-1}{1}=-1[/tex] and [tex] \frac{1}{-1}=-1[/tex]



    if [tex]\sqrt{-1}=i[/tex]








    [tex]\frac{i}{2} + \frac{3}{2i} = \frac{1}{2i} + \frac{3}{2i} [/tex]

    [tex]i(\frac{i}{2} + \frac{3}{2i}) = i(\frac{1}{2i} + \frac{3}{2i})[/tex]


    [tex]\frac{2}{2} = \frac{4}{2}[/tex]

    [tex] 1 = 2 [/tex]
  4. May 29, 2008 #3
    YOu got a problem right here: [tex]\frac{\sqrt{-1}}{\sqrt{1}}=\frac{\sqrt{1}}{\sqrt{-1}}[/tex] Since this gives i=1/i.


    Just because a=b doesn't mean that [tex]\sqrt a = \sqrt b. [/tex]
    Last edited: May 29, 2008
  5. May 29, 2008 #4
    yes it does (as long as we've agreed on some convention so that [tex]\sqrt{x}[/tex] is a function, which we have)

    And that line is correct. The problem is that in the complex numbers [tex]\sqrt{\frac{a}{b}} = \sqrt{\frac{c}{d}}[/tex] does not imply that [tex]\frac{\sqrt{a}}{\sqrt{b}}=\frac{\sqrt{c}}{\sqrt{d}}[/tex]. This is true for the positive real numbers, but not for complex numbers in general.

    But the poster was just asking for "proofs" that 1 = -1. Of course they are all flawed. But to the OP: There are a lot of "proofs" of this, so any more description, if you could remember any part of it, would be useful.
    Last edited: May 29, 2008
  6. May 29, 2008 #5
    Hey Mayday,

    You pretty much have a proof in the one that Dirk_mec1 posted.

    Once you get to this step:


    you now have

    i/1 = 1/i

    multiply both sides by i

    you have (i^2)/1 = i/i --> -1/1 = 1/1 --> -1 = 1.
  7. May 29, 2008 #6
    Thank you! Wait till my class see this stuff!
  8. May 30, 2008 #7
    Another one that freaks people out

    divide by a-b
    since a=b then
    Naturally this is completely fake, the error in this logic is that when you divide by a-b you are dividing by zero. If you want to can keep repeating this and get like 1=4 and stuff. Kinda freaks people out but make sure you explain it to them in the end =P.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook